FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN STUNTING PADA BALITA - Zurhayati Zurhayati; Nurul Hidayah (JOMIS (Journal of Midwifery Science), 2022)
Stunting is one of the nutritional problems that adversely affects the quality of life of children in achieving optimal growth and development according to their genetic potential. Stunting can hinder the process of growth and development in toddlers. Chilhood stunting in childhood is the result of chronic malnutrition or past growth failure and is used as a long-term indicator of childhood malnutrition. Stunting is a health problem that is found in many developing countries, including Indonesia. This study aims to determine the factors associated with the incidence of stunting in children under five in the working area of ​​the UPT Puskesmas Tanjung Batu Kepri. This type of research is quantitative with a correlation analysis research design with a cross-sectional approach. The population in this study were all children under five in the working area of ​​the UPT Puskesmas Tanjung Batu Kepri. The samples were taken as many as 97 children under five using consecutive sampling technique. Data collection using primary data using questionnaires and examinations. The analysis used univariate and bivariate using the chi-square test. The results of the study showed a relationship between education and the incidence of stunting with P-value = 0.15 <0.1. There is a relationship between income and the incidence of stunting with P-value = 0.000 <0.1. There was a relationship between ANC visits and the incidence of stunting with P-value = 0.004 <0.1. It is necessary to increase the provision of information to pregnant women and mothers with children regarding the prevention of stunting.